Komunikasi Kebijakan: Pelarangan Ojek Online Beroperasi Di Jawa Barat - Beltahmamero Simamora (Mahesa Research Center, 2020)
The presence of online transportation has a positive and negative impact on the cycle of socio-economic balance in Indonesian society. In the case of West Java, conventional transportation assesses the presence of online transportation as a threat to their economic income. On the other hand, local governments pay attention to the socio-economic impacts caused by reviewing the available regulatory void. This paper aims to analyze the policy of prohibiting online motorcycle taxis from operating in Central Java through the method of problem formulation and argumentation mapping commonly used in public policy studie as well as how to describe the future, offer policy alternative and policy recommendation regarding the fate of online transportation driver due to the prohibition of operating online transportation in West Java. Data obtained through literature study and documentation studies such as electronic and printed news. The results of this paper found that these problems arose as a consequence of technological developments that were not